2018 Church and clergy tax guide - Hammar, Richard R. (Carol Stream, Illinois : Christianity Today International, 2018)
2013 tax return preparation, 2014 year-round use. The most comprehensive and authoritative tax guide available for both churches and clergy.
Preface -- Introduction -- The income tax return -- Ministers and church staff: employees or self-employed? -- Qualifying as a minister for Federal Tax purposes -- Income -- Exclusions from gross iincome -- Parsonages and housing allowances -- Business expenses, itemized deductions, and credits -- Charitable contributions -- Social security for ministers -- Retirement plans -- Church reporting requirements -- Taxation of churches -- Clergy tax reporting: an illustrated example -- Index.
Keywords: Clergy -- Taxation -- United States; Clergy -- Finance, Personal; Church finance; Income tax -- United States